Unravelling the Impact of an Additional Sex Chromosome in an Adult Female - Sigin George; Vikas Dagar; Barun Kumar Chakrabarty; N. Nagaraja (Journal of Human Reproductive Sciences)
Women with Triple X syndrome (TXS) appear to be at increased risk for decreased ovarian reserve; however, available data are limited. We present an asyndromic adult female with features of recurrent pregnancy loss and decreased ovarian reserve detected with mosaic Triple X syndrome (TXS). The patient was initially evaluated by a low-cost peripheral blood (PB) conventional karyotyping using standard cytogenetic protocols. Interphase fluorescence in situ hybridisation was performed to confirm the diagnosis. Chromosomal microarray, which is a more expensive test, substantiated the presence of additional X chromosomes but failed to detect the presence of low level of mosaicism. Our case study emphasised the recommendation of performing a strategy-based cost-effective cytogenetic evaluation of all cases of decreased ovarian reserve or low anti-Müllerian hormone levels in a resource-constrained setting. It also highlighted the need for additional research to understand the natural history of ovarian function in TXS affected women throughout their lifespans.